2020
DOI: 10.2147/jir.s258839
|View full text |Cite
|
Sign up to set email alerts
|

<p>Microbial Modulation of Coagulation Disorders in Venous Thromboembolism</p>

Abstract: Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is the third leading cause of cardiovascular death in the world. Important risk factors of thrombosis include bed restraint, surgery, major trauma, long journeys, inflammation, pregnancy, and oral contraceptives, previous venous thromboembolism, cancer, and bacterial infections. Sepsis increases the risk of blood clot formation 2-20 times. In this review, we discussed various mechanisms related to the role of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 130 publications
(184 reference statements)
0
9
0
3
Order By: Relevance
“… 11 , 12 It can interact with the physiological processes of host through its metabolic products, such as short-chain fatty acids (SCFAs). 13 , 14 Many studies have shown that the disturbance of gut microbiota has become an important factor in the pathogenesis of depression. 15 , 16 Using nonhuman primate model of depression, researchers found that gut microbiota might participate in the onset of depression through regulating the glycerophospholipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 It can interact with the physiological processes of host through its metabolic products, such as short-chain fatty acids (SCFAs). 13 , 14 Many studies have shown that the disturbance of gut microbiota has become an important factor in the pathogenesis of depression. 15 , 16 Using nonhuman primate model of depression, researchers found that gut microbiota might participate in the onset of depression through regulating the glycerophospholipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have already observed that gut microbiota alter the risk of cardiovascular disease (Witkowski et al, 2020;Jin et al, 2021). Gut microbiota-derived metabolites may increase the risk of venous thromboembolisms (Zhu et al, 2016;Hasan et al, 2020;Lichota et al, 2020). However, the influence of gut microbiota-derived metabolites has not been evaluated in the context of HIT or HITT.…”
Section: Metagenomicsmentioning
confidence: 99%
“…Trimethylamine produced by bacteria is oxidized to trimethylamine-N-oxide (TMAO) by flavin-containing monooxygenase [6]. This enzyme is expressed in the liver and oxidizes xenobiotics containing amines or sulfides [105]. A significantly higher level of this compound was observed in the plasma of CKD patients (30.33 µmol/L) in comparison to the level in healthy subjects (2.08 µmol/L) [106].…”
Section: Other Compoundsmentioning
confidence: 99%
“…Bacterial infections are the leading cause of hospitalization of CKD patients and are related to vascular access, which is the most common source of bacteremia in hemodialyzed patients. Sepsis is associated with an increased risk of thrombosis, myocardial infarction, congestive heart failure, stroke, and peripheral arterial disease [105,141].…”
Section: Implications Of Uremic Toxins and Oxidative Stress In Cardiovascular Diseasementioning
confidence: 99%